Preference for Curvature: A Historical and Conceptual Framework - Gómez-Puerto, Gerardo; Munar, Enric; Nadal, Marcos (Frontiers in Human Neuroscience, 2016)
The idea that curved contours appear to be more pleasurable to the human eye than straight lines is a recurrent theme in aesthetic literature that has been occasionally explored from the scientific psychology. Empirical evidence about preference for curvature is sparse throughout the 20th century. It has not been until the last decade that renewed interest for curvature has arisen. Later studies lend support to the idea that human preference for curved contours could be biologically determined. However, it has also been argued that said preference might be a cultural effect. In this article, we review the available evidence, together with different attempts to explain the nature of preference for curvature: sensoriomotor-based and valuation-based approaches. We also argue that the lack of a unifying framework and clearly defined concepts might be undermining our efforts towards a better understanding of the nature of this phenomenon, and offer a series of unresolved matters as the starting point to further develop a consistent research program.